2016
DOI: 10.4330/wjc.v8.i3.277
|View full text |Cite
|
Sign up to set email alerts
|

Tilt table test today - state of the art

Abstract: A tilt table test (TTT) is an inexpensive, noninvasive tool for the differential diagnosis of syncope and orthostatic intolerance and has good diagnostic yield. The autonomic system malfunction which underlines the reflex syncope is manifested as either hypotension or bradycardia, while an orthostatic challenge is applied. The timing of the response to the orthostatic challenge, as well as the predominant component of the response help to differentiate between various forms of neurocardiogenic syncope, orthost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Over many years of applying tilt tests 26 , 27 and the LBNP method 28 , many devices of varied construction have been used. Most often tilt tables and LBNP chambers were separate devices used in independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Over many years of applying tilt tests 26 , 27 and the LBNP method 28 , many devices of varied construction have been used. Most often tilt tables and LBNP chambers were separate devices used in independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication observed was palpitations, occuring in 13 (18%) patients. (Table 3) Table 1 Results of positive tilt test [13] Generally North Americans prefer isoprenaline while most Europeans use nitroglycerine. Both protocols when compared randomly in one of the studies showed similar results.…”
Section: Resultsmentioning
confidence: 99%
“…For our study, we conducted the HUTT according to our institutional protocol, in which the time and degree of the HUTT is within the range of what has been performed in the published literature. 21,22 Goal measurements The sequence method 23 was used to evaluate baroreceptor reflex function with the focus on three goal measurements. The first goal measurement is the overall activity of the baroreceptors, defined as the number of events per minute.…”
Section: Subjects This Was a Prospective Review Of Cataloged Hutt Datmentioning
confidence: 99%
“…The head upright tilt test (HUTT) is a verified method to evaluate baroreceptor activity changes in both the supine and prone positions. 6,21 This study aims to use the HUTT to discern the variations in the baroreceptor activity during the different phases of measurement and to establish robust normal reference values for the pediatric age group. This study also attempts to define the qualities of the baroreceptors to better describe terminology for future reference.…”
Section: Introductionmentioning
confidence: 99%